3D Hybrid Imaging for Structural and Congenital Heart Interventions in the Cath Lab. Issue 5 (3rd September 2018) - van den Broek, Hans Thijs; van Es, René; Krings, Gregor J.; De Ruiter, Quirina M. B.; Voskuil, Michiel; Meine, Mathias; Loh, Peter; Doevendans, Pieter A.; Chamuleau, Steven A. J.; van Slochteren, Frebus J.
ABSTRACT: Hybrid imaging (HI) during cardiovascular interventions enables the peri-procedural visualization of the organs and tissues by means of integrating different imaging modalities. HI can improve the procedural efficacy and safety. This review provides an overview of different systems, their possibilities and the current clinical use and benefits focused on structural and congenital heart diseases. We have performed a literature search and linked the software options to the clinical use in cardiology to gain insight into the clinical use of the systems. In this review, we focus on radiation and contrast exposure, complication rate and procedure time. We found that currently available studies are limited by small cohorts. Nevertheless, HI systems for valvular procedures result in a significant decrease of radiation and contrast exposure. The largest benefit hereof is observed when HI is used in combination with rotational angiography. Furthermore, automatically determined optimal implant angle for transcatheter aortic valve implantation decreases the complication rate significantly. Congenital heart disease interventions that require 2D/3D Transoesophageal echocardiography (TEE) such as septal defects show a significant decrease in radiation and contrast exposure and procedural time when using TEE-Mono- and bi-plane cine angiography and fluoroscopy (XRF) fusion software. MitraClip procedures using these HI systems, however, show only a trend in decrease of these effects. In conclusion, major interventional X-ray vendors offer HI software solutions which are safe and can aid the planning and image guidance of cardiovascular interventions. Even though current HI technologies have limitations, HI provides support in the increasingly complex cardiac interventional procedures to provide better patient care.